HUBUNGAN ANTARA PARAMETER OSEANOGRAFI DENGAN KANDUNGAN KLOROFIL-a PADA MUSIM TIMUR DI PERAIRAN UTARA PAPUA - Hatta, Muh. (Torani Journal of Fisheries and Marine Science, 2014)
The aims of the research are to determine correlation between chlorophyll a distribution and oceanographyparameter at North Papua Waters dan to identify oceanography parameter which have strong correlation onchlorophyll a distribution especially on East Monsoon. The purpose of the research provide an information aboutthe pattern of chlorophyll a distribution and key oceanography paramater which most affected on chlorophyll aconcentration at the research site. Temperature and salinity were measured using CTD (Conductivity TemperatureDepth) Guildline-6000. Waters ample for measuring chemical paramater was done using Super Rosette Samplerthat have Niskin Bottle that submerge with the CTD. The result showed oceanography parameter affectedsignificantly on chlorophyll a concentration based on depth, chemical parameter. This effect was higher than othereffects in particular on surface water till 200 meter depth. Keywords: oceanography parameters, chlorophyll a distribution, East Moonsoon and North Papua Waters